Neonatal weight loss and gain patterns in caesarean section born infants: integrative systematic review. Issue 2 (27th November 2019) - Kelly, Niamh M.; Keane, Jessica V.; Gallimore, Rachel B.; Bick, Debra; Tribe, Rachel M.
Abstract: There is evidence that caesarean section delivery can impact on neonatal weight loss and weight gain patterns in the first 5 days of life. We conducted an integrative systematic review to examine the association of mode of delivery on early neonatal weight loss. Pubmed, Cumulative Index to Nursing and Allied Health Literature, Web of Science, Excerpta Medica dataBASE, and Medical Literature Analysis and Retrieval System Online were searched for relevant papers published before June 2019. Reference lists from the relevant papers were then backwards and forwards searched. As neonatal weight loss was reported in different formats, a meta‐analysis could not be carried out. Most studies did not distinguish between elective and emergency caesarean sections or instrumental and nonassisted vaginal deliveries. Seven papers were included. All papers except one found that caesarean section was associated with higher weight loss in the early days of life. Two papers presented data from studies on babies followed up to 1 month. One study found that on day 25, babies born by caesarean section had significantly higher weight gain than those born vaginally, while another found that by day 28, babies born vaginally gained more weight per day (11.9 g/kg/day) than those born by caesarean section (10.9 g/kg/day; p = .02). Overall, infants born by caesarean section lost more weight than those born vaginally, but due to the small number of studies included, more are needed to look at this difference and why it may occur. This discrepancy in weight between the two groups may be corrected over time, but future studies will need larger sample sizes and longer follow‐up periods to examine this.